Main crops in middle-west brazilian region: a study of variations from 1975 to 1987 - Yokoiama, Lidia Pacheco; Igreja, Abel Ciro Minniti (Pesquisa Agropecuaria Brasileira, 1992)
Shift-share analysis was used to analyze the growth components for the main crops grown in Central Brazil from 1975 to 1987. The region rapidly increased its relative share in the national agricultural output. The shift-share analysis associated the high growth rates achieved for agricultural production to the following effects: area (EA), yield (ER), geographical localization (ELG), and ratio of crop components in the total production (ECP). That region, recently incorporated to the productive process, does not show EA as the main growth factor observed in the 60's. As a consequence, there is increased relative participation of ER and ECP effect as growth related factors, in the decades of 70 and 80's. These results lead to the conclusion that there has been agricultural modernization, mainly of cash crops, such as soybeans. The increasing impact resulting from the soybean crop expansion detected in the ECP in the shift-share analysis was also noticeable in the individual analysis through the decomposition of area effects, scale effects, and substitution effects.